Memberdayakan Pemuda melalui Pelatihan Hadroh untuk Melestarikan Seni Budaya di Kecamatan Tuminting Kota Manado - Fahmi K; Augustinah, Fedianty; Kamariyah, Sri (AJAD : Jurnal Pengabdian kepada Masyarakat, 2024)
Hadroh is currently less popular among young people, where hadroh contains dhikr and prayers in the activities of the younger generation due to the musicality of songs with pop, rock, and modern nuances and the increasing number of communities that care about preserving traditional arts and culture. The method used is that the data collected is not in the form of numbers, but instead, the data comes from interviews, observations, field notes, and personal documents. Empowering young men and women through hadroh training has increased the skills and understanding of young men and women in the Tuminting Manado sub-district, who increasingly use the art of hadroh musical instruments to preserve cultural arts. As for skills, it can be proven by the skills of young men and women in playing these musical instruments. The skill demonstrated is being more agile or skilled in hand movements when hitting the art to produce musical rhythms that are beautiful to hear. The increasing enthusiasm of young men and women in the Tuminting sub-district of Manado in routine activities after training and mentoring in hadroh arts was held, the young men and women who became players of this traditional art could play this musical instrument well. This is indeed very influential in growing the enthusiasm of other young men and women to participate in revitalizing traditional arts and culture preservation activities.